Концептуальні засади підготовки бакалаврів з маркетингу медицини та фармації - Старих, Любов Володимирівна (My University, 2011)
Проблема підготовки бакалаврів з маркетингу медицини та фармації є актуальною, оскільки ринок України в цілому відчуває нагальну потребу у зазначеного характеру фахівцях. Визначено перспективні напрями підготовки фахівців з маркетингу медицини та фармації шляхом глобального навчання, співпраці з закладами охорони здоров’я, інтеграцією науки й освіти. The problem of training bachelors in medical and pharmaceutical marketing is relevant, since the Ukrainian market as a whole feels an urgent need for specialists of this nature. Promising directions for training specialists in medical and pharmaceutical marketing through global training, cooperation with healthcare institutions, and integration of science and education have been identified.
Keywords: фармація; pharmacy; бакалавр; bachelor; маркетинг медицини; marketing of medicine